Copper Dissolution Rate of Modified Self-Polishing Antifouling Paint with Cerium Oxide - Nikitasari, Arini; Irawan, Januar; Priyotomo, Gadang; J.W. Soedarsono; Riastuti, Rini (Jurnal Sains Materi Indonesia, 2025)
The main objective of the work is to substitute SeaNine 211 in self-polishing antifouling (SPA) paint formulations for marine coating using cerium oxide as a co-biocide. The development of SPA paint with cerium oxide as a co-biocide is expected to significantly improve the environmental friendliness and efficacy of antifouling paints. The preparation of modified SPA paint was undertaken by incorporating the cerium oxide with various concentrations (0.1, 0.3, and 0.5 wt.%) in the SPA paint formulation without SeaNine 211. The copper dissolution rate determines the efficacy of antifouling paint, where the greater the copper release rate, the greater the efficacy of the antifouling paint. The leached-out test results obtained suggest that with an increase of 0.1% wt in the concentration of cerium oxide, there was an improvement in the copper dissolution rate. It was also observed that the mild steel specimens were coated with modified SPA paint when immersed in the seawater for 7 days for testing. The properties were observed by utilizing scanning electron microscopy (SEM). An improvement in the copper dissolution rate was found, as shown by cerium oxide SPA paint when contrasted with bare paint. The contact angle test finding also suggests that adding 0.1% wt of cerium oxide to the SPA paint will increase the dissolution rate of copper. This work could provide insight into developing an environmentally friendly antifouling paint co-biocide.